Factors associated with posttraumatic growth among spouses of women diagnosed with gynaecological cancer: A cross‐sectional study. Issue 2 (30th August 2022) - Zhou, Lihua; Hong, Jingfang; Henricson, Maria; Qin, Rumeng; Dai, Yu; Enskär, Karin; Stenmarker, Margaretha; Browall, Maria
Abstract: Aim: The aim of this study was to explore the factors that are associated with posttraumatic growth among spouses of women diagnosed with gynaecological cancer. Design: A cross‐sectional descriptive study. Methods: A convenience sample of 312 spouses of women diagnosed with gynaecological cancer was recruited from two comprehensive hospitals in China, from March 2018 to March 2020. Demographic characteristics, cancer‐related characteristics, posttraumatic growth, perceived social support and coping were assessed using self‐reported questionnaires. Descriptive statistics and multiple linear regression analysis were performed. The methods were guided by the STROBE checklist. Results: The mean score of posttraumatic growth was 46.7 (standard deviation = 16.7). The associated factors of posttraumatic growth were spouses' age, perceived social support, problem‐focused coping, dysfunctional coping (e.g. denial) and cancer treatment received by partners, which accounted for 34% of total posttraumatic growth score. Patient or public contribution: All participants contributed to the conducting of this study by completing self‐reported questionnaires.